Resilience in Mathematics Learners - Martínez-Padrón, Oswaldo Jesús; De Tejada-Lagonell, Miren Dunixe; García-González, María del Socorro (Revista Electrónica Educare, 2022)
Introduction. A series of aspects related to learners’ resilience of mathematical content are characterized, considering that students can exhibit unfavorable attitudes towards Mathematics. These attitudes restrict the possibility of facing problem-solving in this subject, with cases of students abandoning homework or dropping out of school because they feel aversion towards Mathematics. Objective. To characterize the resilience associated with learners of mathematical content. Analysis. A documentary review was conducted, taking into account, mainly, what has been made visible in the last two decades. It was supported by a qualitative content analysis of issues related to the potentialities that Mathematics learners should have to face mathematical problems and solve them successfully. The study focused on students unable to overcome the difficult situations that usually arise in the mathematics classroom. Results. Among the findings, it is highlighted that resilience occurs in certain contextual conditions and that those who experience it show an impetuous inner compulsion supported by several pillars. These pillars include socio-affective factors such as self-efficacy, perseverance to solve mathematical problems, and, fundamentally, the value that marks the path for the correct action when learners face obstacles until they overcome the circumstance causing the difficulty. Conclusions. It is concluded that every learner of mathematical contents may be resilient if he/she decides to face the extreme situations that may occur in the teaching-learning process of Mathematics.